A Companion to Russian Cinema - Beumers, Birgit (Wiley, 2016)
A Companion to Russian Cinema provides an exhaustive and carefully organised guide to the cinema of pre-Revolutionary Russia, of the Soviet era, as well as post-Soviet Russian cinema, edited by one of the most established and knowledgeable scholars in Russian cinema studies. -- The most up-to-date and thorough coverage of Russian, Soviet and post-Soviet cinema, which also effectively fills gaps in the existing scholarship in the field -- This is the first volume on Russian cinema to explore specifically the history of movie theatres, studios, and educational institutions -- The editor is one of the most established and knowledgeable scholars in Russian cinema studies, and contributions come from leading experts in the field of Russian Studies, Film Studies and Visual Culture -- Chapters consider the arts of scriptwriting, sound, production design, costumes and cinematography -- Provides five portraits of key figures in Soviet and Russia film history, whose works have been somewhat neglected
https://katalog.adlr.link/Record/51-9781118412763